A Paradigm for Well-being The Social Construction of Health in Rural Sri Lanka - Liyanage, C. (My University, 2010)
This chapter attempts to explore the articulation of well-being/ill-being paradigm within the context of rural Sri Lanka. It argues that well-being and ill-being need to be located in the relationship between an understanding of illness and cultural practices. In doing so I look at the space where well-being and ill-being are located within the locus of a village. Illness narratives of the villagers make it abundantly clear that the cosmological order is crucially important in maintaining the social structural hierarchy through their postulation of a well-being/ill-being paradigm. Ethnographic research elucidates the fact that illness is a strategic way for society to perpetuate itself for the smooth running of the social order. These cultural practices reinforce the social hierarchy through well-being/ill-being paradigm. Traditional social relations play a crucial role in maintaining the social order and health and illness in particular have a major share in coordinating these relationships. The empirical evidence of this study highlights the relationship between the space and the healing. Space, therefore become an important fact in understanding the meaning of illness. I argue that illness demands an interpretation 254 Chandani Liyangayethat goes beyond the individual body and specific etiology to enter the context of culture.
Keywords: Well-being; Social Construction; Health; Rural; Sri Lanka